Utility of an attention-based performance validity test for the detection of feigned cognitive dysfunction after acquired brain injury. Issue 3 (15th March 2020) - Fuermaier, Anselm B. M.; Tucha, Oliver; Russ, Dorothea; Ehrenstein, Johanna K.; Stanke, Martin; Heindorf, Ralf; Buggenthin, Rieka; Aschenbrenner, Steffen; Koerts, Janneke; Tucha, Lara
ABSTRACT: Introduction : The Groningen Effort Test (GET) is a recently developed performance validity test (PVT) for the identification of noncredible performance in a neuropsychological assessment of attention abilities. Because the majority of already established PVTs are based on memory functions, the GET has the potential to make a valuable contribution to validity testing. Method : The current study examined the utility of the GET in the detection of feigned cognitive dysfunction after acquired brain injury (ABI) and its incremental validity over already established PVTs, namely the Test of Memory Malingering (TOMM), the Dot Counting Test (DCT), and the b Test. Three hundred and forty-eight participants took part in this study, including 58 patients with ABI (stroke or traumatic brain injury), 43 healthy individuals instructed to show normal behavior, and 247 healthy individuals instructed to feign cognitive dysfunction after ABI. Results : With excellent overall classification accuracy, the GET performed close to the level of the TOMM, and superior to the b Test and DCT. Data analyses further revealed that the GET provides additional diagnostic accuracy compared to the b Test and the DCT in the detection of feigned cognitive dysfunction, but has no incremental validity over the TOMM. For each of the four PVTs in this study, diagnostic sensitivity was independent of the simulation strategy used. Conclusions : It is concluded that the GET is an attention-based PVT with promising test characteristics and high diagnostic accuracy in the detection of noncredible cognitive performance using a simulation design. Given the results can be replicated in studies using known-groups methodology, it may be a useful tool for clinical practice to complement neuropsychological assessments of patients with ABI.